Metal complexes with bis(2-pyridyl)diselenoethers: structural chemistry and catalysis. (10th August 2015) - Cargnelutti, Roberta; da Silva, Felipe Dornelles; Abram, Ulrich; Lang, Ernesto Schulz
Abstract : Bis(2-pyridyl)diselenoethers are versatile ligands for the synthesis of transition metal complexes. Some products show remarkable catalytic activities. Abstract : Bis(2-pyridyl)diselenoethers with the general formula (2-PySe)2 (CH2 ) n [ n = 1, 3 and 4] react with CuI, AgNO3, CuCl2 ·2H2 O and CoCl2 ·6H2 O resulting in the formation of products with molecular or multidimensional structures depending on the stoichiometry of the reactants and the conditions applied. The versatility of this class of selenium-containing ligands is demonstrated with the synthesis and structural characterization of six new complexes of the composition [CuCl2 {(2-PySe)2 CH2 }] n (1 ), [Cu4 I4 {(2-PySe)2 CH2 }2 ] (2 ), [CuCl2 {(2-PySe)2 (CH2 )3 }2 ] (3 ), [CoCl2 {(2-PySe)2 (CH2 )3 }] n (4 ), [Ag{(2-PySe)2 –(CH2 )}3 ] n (NO3 ) n (5 ) and [CuCl2 {(2-PySe)2 (CH2 )4 }] n (6 ), respectively. The Cu(i ) complex (2 ) was tested as catalyst in cross-coupling reactions.